2004
DOI: 10.1532/ijh97.e0309
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Desflurane on Human Platelet Aggregation In Vitro

Abstract: In view of the possible antiplatelet effects of general anesthetics, we investigated the in vitro effects of desflurane, a new inhalation agent, on platelet aggregation. For 15 patients who underwent elective operations, blood was sampled with desflurane induction before and after anesthesia but prior to surgery so that platelet aggregation in the drawn blood could be tested before desflurane anesthesia and again after exposure to the anesthetic. Platelet aggregation was measured with a whole-blood aggregomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…153 Further studies have shown that halothane, [154][155][156] isoflurane, [157][158][159] and desflurane 154 have antiplatelet activity, which may inhibit tumor metastasis to some extent. Paradoxically, under different experimental conditions, these inhaled anesthetics have no effect on platelets 160 or even the opposite effect. 161 Therefore, there is still much work to be done on the effects of inhalation anesthesia on platelet function in tumor research.…”
Section: Other Inhalation Anestheticsmentioning
confidence: 94%
“…153 Further studies have shown that halothane, [154][155][156] isoflurane, [157][158][159] and desflurane 154 have antiplatelet activity, which may inhibit tumor metastasis to some extent. Paradoxically, under different experimental conditions, these inhaled anesthetics have no effect on platelets 160 or even the opposite effect. 161 Therefore, there is still much work to be done on the effects of inhalation anesthesia on platelet function in tumor research.…”
Section: Other Inhalation Anestheticsmentioning
confidence: 94%